1987
DOI: 10.1128/aem.53.6.1241-1245.1987
|View full text |Cite
|
Sign up to set email alerts
|

Comparative survival of antibiotic-resistant and -sensitive fecal indicator bacteria in estuarine water

Abstract: The survival of antibiotic-resistant and-sensitive strains of Escherichia coli, Enterococcus faecalis, Enterococcusfaecium, Streptococcus equinus, and two environmental isolates, AP17 and AQ62, was examined in estuarine water. Each strain was rendered resistant to a combination of two antibiotics by serial passage in increasing concentrations of antibiotics. Cultures were incubated in filter-sterilized estuarine water for up to 7 days. Recovery was assessed by examining colony-forming ability on media with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…However, the decrease in the numbers of culturable bacteria could also be either the result of a loss of culturability or a decrease due to predatory agents besides protozoa, e.g., bacteriophages (5). With respect to culturability, several workers (19,34,38) have cited a decrease in the numbers of culturable enteric bacteria in experiments done in 0.2-,um-pore-size-filtered natural water. Use of FLB allowed us to examine the elimination of specific bacterial species by protozoa in natural waters, since FLB decrease is estimated by direct counts, thus avoiding the problem of culturability of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decrease in the numbers of culturable bacteria could also be either the result of a loss of culturability or a decrease due to predatory agents besides protozoa, e.g., bacteriophages (5). With respect to culturability, several workers (19,34,38) have cited a decrease in the numbers of culturable enteric bacteria in experiments done in 0.2-,um-pore-size-filtered natural water. Use of FLB allowed us to examine the elimination of specific bacterial species by protozoa in natural waters, since FLB decrease is estimated by direct counts, thus avoiding the problem of culturability of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Rif' E. coli K-12 demonstrated membrane protein changes and a decreased ability to colonize germfree mice when in competition with isogenic strains (13). Pettibone et al found that antibiotic-resistant derivatives of fecal indicator organisms displayed altered recovery from wild-type strains in studies of survival in estuarine waters (16). Some antibiotic-resistant mutants of Rhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous antibiotic resistance has provided a potentially simple and effective method to genetically mark bacterial strains for monitoring after introduction into complex ecosystems. Such mutants are being used to study root nodulation and competition among symbiotic nitrogen-fixing strains of rhizobia (2,15), the survival of fecal indicator bacteria in waters (16) and soil (22), and the persistence of organisms of potential use in genetic engineering (10).…”
mentioning
confidence: 99%
“…These microorganisms have developed a complex physiological adaptation strategy that allows them to remain viable over long periods of nutrient deprivation (23,25). Enteric bacteria, introduced into this environment in wastewater effluents, can survive the high salt concentrations and nutrient deprivation for long periods but may not be able to multiply (2,13,28,31,33). The degree of survival depends on the strains of enteric bacteria involved (24,34).…”
mentioning
confidence: 99%